2023
DOI: 10.1002/smll.202300040
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of DNA Nanostructures in Different Cations

Abstract: The programmable nature of DNA allows the construction of custom‐designed static and dynamic nanostructures, and assembly conditions typically require high concentrations of magnesium ions that restricts their applications. In other solution conditions tested for DNA nanostructure assembly, only a limited set of divalent and monovalent ions are used so far (typically Mg2+ and Na+). Here, we investigate the assembly of DNA nanostructures in a wide variety of ions using nanostructures of different sizes: a doubl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Atomic force microscopy (AFM) is typically used for direct imaging and is able to resolve individual origami species, providing insight into the folded character of structures 19 23 . Using this approach, researchers have shown that the folded product of DNA origami can be significantly influenced by design and fabrication conditions such as staple sequences 24 , ionic conditions 25 , and staple-scaffold stoichiometry 26 . While useful, AFM can provide only limited information because it has relatively low temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is typically used for direct imaging and is able to resolve individual origami species, providing insight into the folded character of structures 19 23 . Using this approach, researchers have shown that the folded product of DNA origami can be significantly influenced by design and fabrication conditions such as staple sequences 24 , ionic conditions 25 , and staple-scaffold stoichiometry 26 . While useful, AFM can provide only limited information because it has relatively low temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that assembly in other salts results in enhanced DNA origami stability. 35,36 We probed whether these hollow DNA boxes can be assembled in sodium chloride in the absence of magnesium salts. No dramatic changes were observed when the hollow DNA origami boxes were assembled in sodium chloride ( Supplemental Figure 5C and Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…This may suggest that the hollow DNA origami boxes are either transiently coated by serum components or transiently aggregate. 22,35,37,38 In contrast, other groups have shown that simpler DNA origami structures are considered to be completely dissembled after 24 h in the presence of 10-20% FBS. 22,35,37 However, complete disassembly would not explain the DNA origami box shift back to its original band location after three days.…”
Section: Stabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…An in-plane angle of π/3 rad (60°) is a commonly accepted value in biological contexts [58,59]. This angle is likely to be lower in DNA nanostructures, and may vary between designs, particularly for 2D and 3D structures, and quantification of these angles in origami or other DNA nanostructures has been a subject of few publications, typically in the context of mechanical properties [60], ion dependent reconfiguration [61,62], novel characterization [63][64][65], and bistable physical isomorphs [66,67]. It is worth noting that both the schematics in figure 12, and in most CAD tools, can visually imply larger spacings than occur practically.…”
Section: Decoration Accuracymentioning
confidence: 99%